EWCs in the new Member States. Case study: GM Opel - Jagodziñski, Romuald; Kelemen, Melinda; Neumann, László (Dublin, 2006)
"The joint stock-company General Motors (GM), with its headquarters in Detroit, is the world’s largest automotive group, with nearly 9.2 million vehicles sold around the world in 2005. This case study is based on interviews undertaken with national delegates of the General Motors EWC/GME European Employee Forum (EEF) and with local trade union representatives in Poland and Hungary, and, in addition, with an EWC deputy member from Poland. The interviews were carried out between February and July 2006. The EWC, which is known as GME European Employee Forum (EEF), was established by a voluntary agreement in 1996."